New evidence on the earliest human presence in the urban area of Genoa (Liguria, Italy): A multi-proxy study of a mid-Holocene deposit at the mouth of the Bisagno river. (December 2018) - Arobba, Daniele; Caramiello, Rosanna; Firpo, Marco; Mercalli, Luca; Morandi, Lionello F; Rossi, Stefano
The article presents the results of a multi-proxy study investigating an alluvial deposit located in the coastal plain of Genoa (Liguria, Northwest Italy). A very deep core was sampled from 15 to 25 m below ground level to analyse sedimentological properties, pollen assemblages, non-pollen palynomorphs, plant macrofossils and micro-charcoal. The deposit, spanning from the second half of the 5th Millennium to the end of the 7th Millennium cal. BC, was characterized by an alternation of silty and peaty layers, and proved to be rich in plant remains. Pollen data allowed the confirmation of a gradual increase in Fagus sylvatica to the detriment of Abies alba during the mid-Holocene of the region, and showed the presence of brackish lagoons, as well as the progressively stronger incidence of anthropogenic taxa, indicating the use of the plain for agricultural purposes. The study of non-pollen palynomorphs led to the taxonomic identification of some previously unidentified types, and pointed to the occurrence of marshy environments, which were probably grazed on by domestic herbivores. Macrofossil analysis provided the first record of Triticum new glume wheat type in Liguria. Moreover, the finding of a grain of Triticum dicoccum dated to the second half of the 6th Millennium cal. BC allowed us to pre-date by seven centuries the agriculture in the region. To date, this represents the oldest evidence of human activity in the urban area of Genoa.